PEMBINAAN REMAJA GKPM BETAET KECAMATAN SIBERUT BARAT MEMAHAMI DAN MELAKUKAN PESAN KITAB SUCI - Mangentang, Matheus; Sinaga, Arilamson; Pasaribu, Novelia; Hutahaean, Hasahatan (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
The Bible is a series of writings that God has given to man. In the Christian faith, the Bible is the Word of God and through it, the people can know what is in God's heart. However, to understand the Bible, we must use various ways to make the writings in it easy to understand. One village that faces directly from the Indian Ocean Betaet needs to be considered in the development of faith and spirituality. In Betaet village, the composition of the Christian and Muslim populations has gone hand in hand in the last five years. The PkM team took the segment of the youth and youth categories to become a coaching community. Coaching activities are given after first observing what is needed for coaching in Betaet. With the lecture and semi-workshop method, the PkM Team guides teenagers and youth at the GKPM Betaet Church After participating in the coaching, adolescents and young men have a practical, simple, and easy method of understanding the Bible that encourages them to regularly read the Bible in their respective homes. Thirty-six participants who took part in the training felt a change in their lives and were determined to live in faith in Christ Jesus alone. It is hoped that similar activities will be given in Betaet for the category of Mother, Father, and children so that they have a fresh, strong, and agile spiritual life in Christ Jesus every day.